Detecting Brain Activity Following a Verbal Command in Patients With Disorders of Consciousness - Wang, Fuyan; Hu, Nantu; Hu, Xiaohua; Jing, Shan; Heine, Lizette; Thibaut, Aurore; Huang, Wangshan; Yan, Yifan; Wang, Jing; Schnakers, Caroline; Laureys, Steven; Di, Haibo (Frontiers in Neuroscience, 2019)
Background: The accurate assessment of patients with disorders of consciousness is a challenge to most experienced clinicians. As a potential clinical tool, functional magnetic resonance imaging (fMRI) could detect residual awareness without the need for the patients’ actual motor responses. Methods: We adopted a simple active fMRI motor paradigm (hand raising) to detect residual awareness in these patients. Thirty patients were recruited. They met the diagnosis of minimally conscious state (MCS) (male = 6, female = 2; n = 8), vegetative state/unresponsive wakefulness syndrome (VS/UWS) (male = 17, female = 4; n = 21), and emergence from a MCS (EMCS) (male = 1; n = 1). Results: We analyzed the command-following responses for robust evidence of appropriate, consistent, and statistically reliable markers of motor execution, similar to those noted in 15 healthy controls. Of the 30 patients, five (one EMCS, two MCS, two VS/UWS) were able to modulate their brain activity to the ‘hand-raising’ command, and they showed activation in motor-related regions (which could not be discovered in the own-name task). Conclusions: Longitudinal behavioral assessments showed that, of these five patients, two in a VS/UWS evolved to MCS and one from MCS evolved to MCS+ (i.e., showed command following). The simple active fMRI ‘hand-raising’ task can elicit brain activation in patients with disorders of consciousness, similar to those observed in healthy volunteers. Activity of the motor-related network may serve as an indicator of high-level cognition that cannot be discerned through conventional behavioral assessment.